KETERAMPILAN GEOMETRI SISWA DALAM MENYELESAIKAN SOAL PERSEGI DAN PERSEGI PANJANG - Dwi Cahyati Ramadhani; Agung Hartoyo; Dian Ahmad BS (Jurnal AlphaEuclidEdu, 2023)
The study aimed to identify and described student geometry in solving square and rectangular problems. The method used was case study with qualitative approach. The subject are three students in class VII E SMP Negeri 7 Sungai Raya. Data collection used in this study was a geometry skill test and a non-test technique, interview. The analysis of data revealed that three students fulfilled with visual and verbal skill, two students fulfilled with drawing skill, one student each fulfilled with logical skill and applied skill.  In visual skill, students could identify names and basic information of square and rectangle. In verbal skill, students could write the names and properties of square and rectangle. In drawing skill, students could sketch the figure based on the given information. In logical skill, students couldn’t explain the relationship between properties of figure, it caused that the students can define the figure, but do not connected the same properties between square and rectangle. In applied skills, students do not applied the concepts related to square and rectangle in daily life. Additionally, the students also didn’t apllied logical thinking related to the construct of square and rectangle.